Pengembangan Media Video Pembelajaran Angklung Untuk Materi Alat Musik Sederhana Kelas V SDN 10 Simpang Teritip - Zikri Aprillah Pratama; Maulina Hendrik; Feri Ardiansah (Universitas Muhammadiyah Bangka Belitung, 2025)
Students' struggles in recognizing learning related to musical instruments, especially basic information about musical instruments, was the driving force for this research. This is due to inadequate facilities and infrastructure to carry out the SBdP learning activity process. The aim of this research is to create an angklung learning video media product that is useful and valid for SBdP learning. This research uses the ADDIE approach to research and development (R&D). Six students were the subjects of the study's small-scale trials, while twenty students participated in the large-scale trials. To obtain data, questionnaires and interviews were carried out. Analysis of student responses, analysis of teacher practitioner questionnaires, and validation analysis of expert questionnaires are the data analysis methods used. Media experts received an assessment of 87.5% in the